Development of a dual vaccine against East Coast fever and lumpy skin disease - Whittle, Leah; Chapman, Ros; Douglass, Nicola; Jaffer, Mohamed; Margolin, Emmanuel; Rybicki, Edward; Williamson, Anna-Lise (Frontiers in Immunology, 2023)
East Coast fever is an acute bovine disease caused by the apicomplexan parasite Theileria parva and is regarded as one of the most important tick-vectored diseases in Africa. The current vaccination procedure has many drawbacks, as it involves the use of live T. parva sporozoites. As a novel vaccination strategy, we have constructed the recombinant lumpy skin disease virus (LSDV) named LSDV-SODis-p67HA-BLV-Gag, encoding a modified form of the T. parva p67 surface antigen (p67HA), as well as the bovine leukaemia virus (BLV) gag gene for the formation of virus-like particles (VLPs) to potentially enhance p67 immunogenicity. In place of the native sequence, the chimeric p67HA antigen has the human tissue plasminogen activator signal sequence and the influenza hemagglutinin A2 transmembrane domain and cytoplasmic tail. p67HA was detected on the surface of infected cells, and VLPs comprising BLV Gag and p67HA were produced. We also show that higher multiple bands observed in western blot analysis are due to glycosylation of p67. The two vaccines, pMExT-p67HA (DNA) and LSDV-SODis-p67HA-BLV-Gag, were tested for immunogenicity in mice. p67-binding antibodies were produced by vaccinated animals, with higher titers detected in mice vaccinated with the recombinant LSDV. This candidate dual vaccine warrants further testing in cattle.